Atlas of synovial fluid analysis and crystal identification / H Ralph Schumacher; Antonio J Reginato - Schumacher, H. Ralph
This atlas aims to provide a detailed description of the gross and microscopic examination of synovial fluid and its cytology with special emphasis on crystal identification.